ผลขอลการใช้ Clinical Practice Guideline (CPG) ร่วมกับ Care Map ต่อการปฏิบัติกิจวัตรประจำวันในผู้ป่วยโรคหลอดเลือดสมอง โรงพยาบาลอู่ทอง จังหวัดสุพรรณบุรี - Nilpetchploy, Ratana (วารสารแพทย์เขต 4-5, 2018)
Background: Cerebrovascular disease (stroke) is a neurological defect. This disease affects the patient, family and country. The most patients are impacted on losing the ability to perform activities of daily living by themselves. Caregivers are important for helping these patients to perform any activities that they cannot perform and must have the knowledge and skill to prevent complications including psychosocial care. The role of physicians to improve patients’ care as they focused on bringing the Clinical Practice Guideline (CPG) and care map to guide for caring these patients. The objective: This study was the quasi-experimental study to study the effectiveness of this CPG with care map for stroke to evaluate the activities of daily living (ADL) in stroke patients, and to compare these results before and after using of CPG with care map to assess ADL in stroke patients at U-thong hospital, Suphan Buri province. A total of 52 patients were collected since 1st October 2010 to 30th September 2011. Tools for using to collect data were questionnaires’ Barthel Index (BI) and questionnaires’ ability of caregiver to care of stroke patients. The data were analyzed by using average, percent, standard deviation and inferential statistics (paired t- test). Result: This study showed that the comparison of the Barthel ADL Index (BI) of stroke patients before using of CPG with care map to assess ADL, the scores were 25.67 (range from 25 to 45) implied almost all ADL depended on caregivers. After using of CPG with care map to assess ADL, the scores were 63.80 (range from 50 to 70) showed that half of ADL depend on caregivers. This comparison showed statistically significant difference at 0.05 level (p = .00). Recommendation: the other study should be implemented the other questionnaires for evaluate with BI such as, Modified Rankin Scale (MRS) and questionnaires’ SS-QOL (Stroke-Specific Quality of Life), to measure the ability of patients more than ADL for improvement the stroke patient care in hospital.